El piso es lava: la Corte Suprema de Justicia de la Nación en 2022 - Arballo, Gustavo (2022)
This work presents an overview of the relevant rulings of the Argentine Supreme Court for the year 2022. The reviewed rulings are organized by theme and briefly described to explain the basis and implications of the decisions. Each chapter aims to identify and describe statements, evolutions, innovations, and areas of uncertainty in the Court?s recent rulings. This essay covers political cases, important interpretive decisions, and rulings that reveal discontinuities and "atypical" decisions. The final chapters seek to point out some features for theorizing and analyzing the case law of higher courts in convoluted contexts